Implementasi Robot Orang-Orangan Sawah Supply Energi Matahari Memakai Microcontroller - Ahmad Dahlan Simanjuntak; Jhonson Efendi Hutagalung; Abdul Karim Syahputra (Forum Kerjasama Pendidikan Tinggi, 2022)
Sparrows are a type of pest that is very detrimental to rice farmers, even though these bird pests are small in size but in very large numbers, causing rice farmers to be overwhelmed in protecting rice from pests. Efforts made by farmers in protecting rice from bird pests by using scarecrows that work less effectively, it is necessary to have a scarecrow robot that can work effectively by utilizing solar heat as an energy supply. The rice field robot will be placed in the middle of the rice field that has issued a grain with a size of 20mx20m by utilizing the LDR sensor as a switch to turn on and off automatically, where the robot is equipped with 4 sound sensors placed in each corner of the rice field to detect the sound of birds on the ground. when the robot's sound sensor detects the sound of bird pests, the DC motor mounted on the robot body will move to rotate the robot body left and right along with the servo installed on the two robot arms will move in opposite directions from 00-1800 or 1800-00 and the DFPlayer will make a sound to scare away bird pests that will attack rice. Finally, the author hopes that this research can be further developed so that it can increase the use of the robot in bird repellent